2015
DOI: 10.1371/journal.pone.0124150
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila Model Identifies a Critical Role for Zinc in Mineralization for Kidney Stone Disease

Abstract: Ectopic calcification is a driving force for a variety of diseases, including kidney stones and atherosclerosis, but initiating factors remain largely unknown. Given its importance in seemingly divergent disease processes, identifying fundamental principal actors for ectopic calcification may have broad translational significance. Here we establish a Drosophila melanogaster model for ectopic calcification by inhibiting xanthine dehydrogenase whose deficiency leads to kidney stones in humans and dogs. Micro X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 63 publications
4
69
0
Order By: Relevance
“…5) [79]. This study also demonstrated that pharmacologic inhibition of XDH with allopurinol yielded similar tubule concretions.…”
Section: Xanthinuriasupporting
confidence: 69%
See 3 more Smart Citations
“…5) [79]. This study also demonstrated that pharmacologic inhibition of XDH with allopurinol yielded similar tubule concretions.…”
Section: Xanthinuriasupporting
confidence: 69%
“…The conventional method to determining stone composition, Fourier Transform Infrared Spectroscopy (FTIR), demonstrated that Xdh knockdown fly stones contained xanthine [79]. However, using targeted metabolomics, these stones were also found to contain hypoxanthine.…”
Section: Stone Composition 441 Calcium Oxalate and Hydroxyapatitementioning
confidence: 99%
See 2 more Smart Citations
“…24 Chi et al proposed that zinc facilitates calcification given the presence of non-trace levels of zinc in fly crystals, human xanthine stones and CaOx plaques. By inhibiting zinc transporter genes a suppression of Drosophila crystals formation were observed.…”
Section: Discussionmentioning
confidence: 99%